Enriching or Depleting? The Dynamics of Engagement in Work and Family Roles. - Rothbard, Nancy P. (Administrative Science Quarterly, 2001)
This study develops a model of engagement in the multiple roles of work and family. I examine two competing arguments about the effects of engaging in multiple roles, depletion and enrichment, and integrate them by identifying the type of emotional response to a role, negative or positive, as a critical contrasting assumption held by these two perspectives. Moreover, I represent depletion and enrichment as complex multistep processes that include multiple constructs, such as engagement and emotion. This study jointly examines both the depleting and enriching processes that link engagement in one role to engagement in another, using structural equation modeling. Findings from a survey of 790 employees reveal evidence for both depletion and enrichment as well as gender differences. Specifically, depletion existed only for women and only in the work-to-family direction. Men experienced enrichment from work to family, while women experienced enrichment from family to work. Overall, more linkages were found between work and family for women than for men. Reprinted by permission of the publisher.